Marketing in Venus : perspectives from the heart - Kartajaya, Hermawan; Md. Sidin, Samsinar (Universiti Putra Malaysia Press, 2011)
Marketing in Venus: Perspectives from the Heart is a book on Marketing with the emotional attachment. It emphasizes the importance of passion in marketing your products and services. We believe that using the 4Ps alone is not sufficient to be successful in what we want to do in this Earth that has become Venus. In Venus, people are emotional, and we have to look at what the customers’ want, and get deep into their hearts, digging their ultimate latent motivation of their intents. Only doing those things that we can actually make the customers really happy, satisfied and consequently loyal to our products and services. As Earth has become Venus, previous approaches, business models, strategies and tactics which were once sure solutions have become obsolete. It is our aim to target the readers’ heart. The chapters, discussions, examples and tips are all aimed at heightening the readers’ emotional attachment to the products; whether it was the products that they purchased or products that they are selling. This book is positioned to be an applied Marketing book with conceptual and applied perspectives. It can be read by both marketers and consumers. It has 18 chapters, consistent with the 18 guiding principles of Marketing in Venus. In each chapter, there are many examples, some even extended to be ‘the story’. This book is the Malaysian version of the original book Marketing in Venus by Hermawan Kertajaya with necessary updates to suit today’s environment.